Challenges on Party Institutionalization - Trinanda, Ghea Anissah; Astanujati, Nicolas Kriswinara (PCD Journal, 2023)
This article explores institutionalization challenges in the National Democrats (NasDem) Party in promoting the Renewable Energy Bill, viewed from the party’s three faces. NasDem is strategically involved in policy decision-making in the Indonesian parliament, but the three faces of the party are yet to be seen. Despite being established over a decade ago, the direction of institutionalization is still transforming, especially in the linkage between public office and the party at the grassroots. The research question is: How do the three faces of the party in NasDem impact the challenges of institutionalization? Drawing from the Renewable Energy Bill case studies, we argue that three challenges exist. First, a personalistic party’s strong influence leads to failure in two-way communications, especially at the grassroots. Second, the vision of the renewable energy law was not implemented at the grassroots because the party had to focus on regional policies. Third, although the renewable energy vision has not been fully implemented, the idea of ‘green politics’ has been realized by the party wing at the grassroots through the political education program.